Autophagy as a Therapeutic Target in Breast Tumors: The Cancer stem cell perspective - Sana Raza; Jawed Akhtar Siddiqui; Anubhav Srivastava; Naibedya Chattopadhyay; Rohit Anthony Sinha; Bandana Chakravarti (Autophagy Reports)
Breast cancer is a heterogeneous disease, with a subpopulation of tumor cells known as breast cancer stem cells (BCSCs) with self-renewal and differentiation abilities that play a critical role in tumor initiation, progression, and therapy resistance. The tumor microenvironment (TME) is a complex area where diverse cancer cells reside creating a highly interactive environment with secreted factors, and the extracellular matrix. Autophagy, a cellular self-digestion process, influences dynamic cellular processes in the tumor TME integrating diverse signals that regulate tumor development and heterogeneity. Autophagy acts as a double-edged sword in the breast TME, with both tumor-promoting and tumor-suppressing roles. Autophagy promotes breast tumorigenesis by regulating tumor cell survival, migration and invasion, metabolic reprogramming, and epithelial-mesenchymal transition (EMT). BCSCs harness autophagy to maintain stemness properties, evade immune surveillance, and resist therapeutic interventions. Conversely, excessive, or dysregulated autophagy may lead to BCSC differentiation or cell death, offering a potential avenue for therapeutic exploration. The molecular mechanisms that regulate autophagy in BCSCs including the mammalian target of rapamycin (mTOR), AMPK, and Beclin-1 signaling pathways may be potential targets for pharmacological intervention in breast cancer. This review provides a comprehensive overview of the relationship between autophagy and BCSCs, highlighting recent advancements in our understanding of their interplay. We also discuss the current state of autophagy-targeting agents and their preclinical and clinical development in BCSCs.